The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/0008-5472.can-13-1672
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Melanoma Sentinel Nodes Identify Patients with Poor Outcome and Reveal an Association of CD30+ T Lymphocytes with Progression

Abstract: Sentinel lymph nodes set the stance of the immune system to a localized tumor and are often the first site to be colonized by neoplastic cells that metastasize. To investigate how the presence of neoplastic cells in sentinel lymph nodes may trigger pathways associated with metastatic progression, we analyzed the transcriptional profiles of archival sentinel node biopsy specimens obtained from melanoma patients. Biopsies from positive nodes were selected for comparable tumor infiltration, presence or absence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…markers of immune infiltration as positive predictors of distant metastasis and unfavourable overall survival 37 .…”
Section: Modified Oncolytic Herpes Virusmentioning
confidence: 99%
“…markers of immune infiltration as positive predictors of distant metastasis and unfavourable overall survival 37 .…”
Section: Modified Oncolytic Herpes Virusmentioning
confidence: 99%
“…RNA extraction, quality control, and hybridization on a Whole Genome-cDNAmediated Annealing, Selection, extension, and Ligation (WG-DASL) microarray were performed essentially as previously described (3). Raw data were deposited with accession number GSE65021 on GEO repository (http://www.ncbi.nlm.nih.gov/ geo/).…”
Section: Whole Genome Gene-expression Profilingmentioning
confidence: 99%
“…56 A prospective study of Foxp3 + regulatory T cells and DCs in melanoma SNs showed correlations between node positivity and increased regulatory T cells or decreased dendritic cells. 57 Vallacchi et al, 58 using gene expression profiling of melanoma SNs and by unsupervised analysis of gene expression profiles, found "immune response" to be a major gene ontogeny represented.…”
Section: Evidence Of Sn Immune Modulation In Melanoma and Breast Cancermentioning
confidence: 99%